Enhancement of photocatalytic Cr(VI) reduction using mandarin peel extract as natural sacrificing agent - Lee, Youn Jun; Son, Chae Young; Lee, Chang Gu; Jae Jeong, Yoo; Sun Cho, In; Park, Seong Jik; Lee, Jechan (Alexandria Engineering Journal, 2023)
In a photocatalytic Cr(VI) reduction system, a hole scavenger (electron donor) is required to enhance the performance of photocatalytic reaction. In this study, mandarin peel extract (ME) was used as a natural sacrificing agent to enhance the photocatalytic Cr(VI) removal performance. The use of ME increased the Cr(VI) reduction rate (0.0286 min−1), and a Cr(VI) removal efficiency of 99.1% was achieved within 150 min. Hole scavenging by antioxidants contained in ME on TiO2 surface contributed to the enhancement of the photocatalytic Cr(VI) removal. Under the optimal conditions (ME volume = 5 mL, TiO2 dose = 0.2 g L−1, and pH = 2), the Cr(VI) reduction rate constant was about 1.2–7.3 times higher than the values reported in the literature. Furthermore, experiments on Cr(VI) treatment in real wastewater and H2O2 production showed the suitability of ME for other reaction systems. The photocatalytic Cr(VI) reduction efficiency achieved in 150 min in real wastewater increased from 58.6% to 83.6% after ME addition. This study employed a waste material as a reagent to improve the photocatalytic Cr(VI) removal performance for the photoreduction of a water pollutant, namely Cr(VI), which can be employed as a strategy for simultaneous waste and water treatment.
Keywords: % reductions; Cr(VI) photocatalytic reduction; H2O2 production; Hole scavenger; Mandarin peel; Photo-catalytic; Photocatalytic reduction; Real wastewater; Reduction rate; Removal performance; Cr(VI) photocatalytic reduction; H2O2 production; Hole scavenger; Mandarin peel; Wastewater treatment